Biotic interactions, energy pathways and trigger factors of ecosystem dynamics in shallow saline lakes - Golubkov, Sergei M.; Golubkov, Mikhail S.; Balushkina, Evgenia V.; Litvinchuk, Larisa F. (Studia Ecologiae et Bioethicae, 2014)
Environmental variables, food-web dynamics, and energy pathways were investigated in ecosystems of six shallow lakes of the Crimea with salinity ranging from 24 to 340‰. There were considerable inter- and intra-annual #uctuations in the abiotic characteristics of the lakes. All the lakes had a very high concentration of total phosphorus in the water (up to 5.6 gP m-3) due to a great influence of the watershed on the lakes. A high level of primary production (up to 14.9 gC m-2 d-1) was found in the most of the lakes. The lowest primary production was found in the most saline lake with a dense population of the filtrator, Artemia urmiana. Grazing benthic energy pathways were dominant at salinities between 24 and 58‰. Greater levels of salinity led to a gradual reduction of benthic and increase of planktonic energy pathways. A fast shift from turbid to the clear-water regime was observed in one of the lakes, caused by annual variations in weather conditions.